Belatacept As an Alternative to Calcineurin Inhibitors in Patients with Solid Organ Transplants - Kumar, Dhiren; LeCorchick, Spencer; Gupta, Gaurav (Frontiers in Medicine, 2017)
The goal of immunosuppression in transplantation has shifted to improving long term outcomes, reducing drug induced toxicities while preserving the already excellent short term outcomes. Long term gains in solid organ transplantation have been limited at least partly due to the nephrotoxicity and metabolic side effects of calcineurin inhibitors (CNIs). The alloimmune response requires activation of the costimulatory pathway for T cell proliferation and amplification. Belatacept is a molecule that selectively blocks T cell costimulation. In June 2011, the U.S. Food and Drug Administration approved it for maintenance immunosuppression in kidney transplantation based on two open-label, randomized, Phase III trials. Since its introduction, belatacept has shown promise in both short and long term renal transplant outcomes in several other trials. It exhibits a superior side effect profile compared to CNIs with a comparable efficacy. Across all solid organ transplants, the burden of chronic kidney disease, its associated cardiovascular morbidity, mortality, and inferior patient/allograft survival is a well-documented problem. In this review we aim to discuss the evidence behind the use of belatacept in solid organ transplants as an effective alternative to calcineurin inhibitors for renal rescue in patients with acute and/or chronic kidney injury.